The liberation of women and girls as the liberation of Mother Earth: A theological discourse - Chireshe, Excellent (HTS teologiese studies, 2023)
This article, grounded in ecofeminism, considers the earth as symbolising women and girls and the liberation of women and girls as the liberation of the earth. When the environment is liberated from abuse, its capacity to sustain human life is enhanced. In the same way, when women and girls are freed from all forms of oppression and exploitation and are allowed to be self-actualising people, their capacity to contribute meaningfully to sustainable development and human welfare is enhanced. Given that women and girls play key culturally prescribed roles such as being carriers of life through childbirth, nurturing, caregiving and serving as pillars of the home, their oppression and exploitation stifle their contribution to societal development, thereby curtailing sustainable development. Similarly, abuse of the earth results in environmental crises such as floods, droughts, famine, heat waves and global warming, resulting in the earth’s diminished capacity to sustain life. This study was based on literature review and informal interviews involving participants from three churches (the Reformed Church in Zimbabwe, the Apostolic Faith Mission in Zimbabwe and the Johanne Marange Apostolic Church). This article examined the extent to which religion can empower women to participate in public activities including environmental management, epitomised by the way women and girls in the selected churches are perceived and treated. It is concluded that religion can be both liberating and binding to women and girls and, by implication, Mother Earth.Contribution: This article highlights parallels between females and Mother Earth, using the treatment of women and girls in three churches as the springboard of the discussion. It considers how far such treatment can promote their participation in public spheres that include taking care of and managing the environment.